2016
DOI: 10.21236/ad1013241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biodiesel Fuels to Reduce Fossil Fuel Use in Corps of Engineers Floating Plant Operations

Abstract: A study to evaluate the feasibility of using biodiesel fuel in U.S. Army Corps of Engineers (USACE) floating plant operations to reduce environmentally sensitive emissions, increase use of renewable energy, and reduce the use of fossil fuels was conducted with funding from the U.S. Army Corps of Engineers (USACE) Dredging Operations and Environmental Research (DOER) program and the USACE Sustainability and Energy Efficiency Program. This study was conducted by the USACE Engineer Research and Development Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In 2013, the USACE Engineer Research and Development Center published results of emissions testing using the three described fuels above in USACE‐owned navigation equipment . The use‐phase in the current study used reported fuel consumption rates and emissions from two vessels (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2013, the USACE Engineer Research and Development Center published results of emissions testing using the three described fuels above in USACE‐owned navigation equipment . The use‐phase in the current study used reported fuel consumption rates and emissions from two vessels (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although USACE relies heavily on privately owned and operated dredging equipment for much of this work, it holds 2300 floating plant assets. In 2010, fuel consumption for these assets alone was 8.3 million gallons of diesel …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diesel and Biodiesel use in Navigation Equipment. Tubman et al (2016) measured emissions from the operation of USACE-owned debris boats using three different fuels, to explore the utility of using biofuels in navigation equipment to reduce carbon emissions and increase use of renewable resources. This was valuable for documenting use-stage outputs.…”
Section: Application Of Lca and Case Studies For The Navigation Programmentioning
confidence: 99%